Determination of the Water Value of a Snow Cover With Radioactive Substances - Fischmeister, Viktor (1970)
The concept of the water value is defined and the determination of the water value with the conventional snow gauge explained. On the basis of a schematic diagram the mode of operation of the radiation sound and the arrangement of an experimental apparatus are described. Then the calibration and testing of the experimental apparatus is recounted and a criticism is offered of the testing procedure, of the method of measurement, and of the experimental apparatus. The article closes with a general reference to the handling of radioactive materials and the precautionary measures necessary in working with them. Trans. of Wasserwirtschaft (Austria) v8 n4 p86-93 Apr 1956.